Survival and complications of monolithic ceramic for tooth-supported fixed dental prostheses: A systematic review and meta-analysis - Mazza, Letícia Cerri [UNESP]; Lemos, Cleidiel Aparecido Araujo; Pesqueira, Aldiéris Alves [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Elsevier, 2021)
Statement of problem: Although recent studies have reported the success of implant-supported monolithic restorations, consensus on the use of monolithic ceramic restorations is lacking. Purpose: The purpose of this systematic review and meta-analysis was to evaluate the survival and biological and technical complication rates of monolithic single crowns and fixed partial dentures (FPDs). Material and methods: An electronic search was conducted by 2 independent authors on the PubMed/MEDLINE, Scopus, and Cochrane Library databases. The Newcastle-Ottawa scale and Cochrane risk of bias tool were used to assess the quality and risk of bias of the included studies. Meta-analysis was performed by using the R software program. Results: The search identified 763 articles, 18 of which met the eligibility criteria. A total of 15 studies evaluated monolithic ceramic single crowns, and 4 studies evaluated FPDs. The studies included 1061 monolithic single crowns (524 lithium disilicate, 461 zirconia, and 76 polymer-infiltrated ceramic network [PICN]) and 104 FPDs (36 lithium disilicate and 68 zirconia). Meta-analysis of single-arm studies indicated the proportion of survival, biological, and technical complication rates of 1% (95% confidence interval [CI]: 0% to 3%), 1% (CI: 0% to 4%), and 2% (CI: 1% to 4%), respectively, for single crowns, independent of ceramic material, and 3% (CI: 0% to 34%), 5% (CI: 1% to 21%), and 5% (CI: 1% to 21%) for FPDs, respectively. Only 5 studies performed a direct comparison between monolithic and veneered ceramic restorations, and no significant difference was observed in terms of survival (risk ratio [RR]: 0.68; CI: 0.25-1.91; P=.96), biological (RR: 0.69; CI: 0.31-1.53; P=.35), and technical complication rates (RR: 0.87; CI: 0.40-1.88; P=.29). Conclusions: The use of monolithic ceramic can be considered a favorable treatment for tooth-supported single crowns and FPDs, with high survival and low complication rates. However, further randomized controlled trials are needed to reassess these clinical performances, mainly by comparing them with the performance of veneered restorations.